Bullous Pemphigoid IgG Induces Cell Dysfunction and Enhances the Motility of Epidermal Keratinocytes via Rac1/Proteasome Activation - Tie, Duerna; Da, Xia; Natsuga, Ken; Yamada, Nanako; Yamamoto, Osamu; Morita, Eishin (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) is an autoimmune disease characterized by the formation of blisters, in which autoantibodies mainly target type XVII collagen (ColXVII) expressed in basal keratinocytes. BP IgG is known to induce the internalization of ColXVII from the plasma membrane of keratinocytes through macropinocytosis. However, the cellular dynamics following ColXVII internalization have not been completely elucidated. BP IgGs exert a precise effect on cultured keratinocytes, and the morphological/functional changes in BP IgG-stimulated cells lead to the subepidermal blistering associated with BP pathogenesis. Based on the electron microscopy examination, BP IgG-stimulated cells exhibit alterations in the cell membrane structure and the accumulation of intracellular vesicles. These morphological changes in the BP IgG-stimulated cells are accompanied by dysfunctional mitochondria, increased production of reactive oxygen species, increased motility, and detachment. BP IgG triggers the cascade leading to metabolic impairments and stimulates cell migration in the treated keratinocytes. These cellular alterations are reversed by pharmacological inhibitors of Rac1 or the proteasome pathway, suggesting that Rac1 and proteasome activation are involved in the effects of BP IgGs on cultured keratinocytes. Our study highlights the role of keratinocyte kinetics in the direct functions of IgG in patients with BP.